Land Characteristics And Land Evaluation For Development On Other Use Area Rice Fertilizer Plants In District Salak Regency Pakpak Bharat - Fitra Syawal Harahap; Darmadi Erwin Harahap; Parmanoan Harahap (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
The opening of new areas should be investigated so that land resources can be used to determine the suitability of the land on certain uses so that APL land use (Other Area of Use) in Salak Sub-district needs to be supported with information on land suitability. The objectives of this study were to evaluate the characteristics of the APL land suitability level, to analyze improvement efforts to increase productivity and to create an actual land suitability map and potential land suitability for Wetland rice on APL land in Kecamatan Salak. The research method used the survey method. Unit of land-based on land map. Research data were analyzed using the matching method. Characteristics of the land in Salak District both physical and chemical properties have very diverse characteristics that can be inhibiting or supporting factors in the development of agricultural crops, especially the development of rice paddy. Temperature regime limiting factor (tc), rooting medium (rc), erosion hazard (eh). Improvement efforts that can be done are pelumpuran, giving of organic material, making of the terrace, and fertilizing. Temperature regime can not be repaired